MNU representa Zumbi (1970-2005): cultura histórica, movimento negro e ensino de história - Amorim, Alessandro Moura de (2011)
This research aimed to do an appreciation of the historical representations (historiography and historical culture) of a black protagonist of the seventeenth century, Zumbi dos Palmares, produced between 1970 and 2005. The analysis was around of the intellectual production (Clovis Moura, Decio Freitas, Birth and Joel Rufino dos Santos) and of the performance of the leaderships of the Black Movement Unified (MNU), established in 1978 (Amauri Mendes Pereira, Edson Cardoso, Helena Machado, Marcos Cardoso, Milton Barbosa, Yedo Ferreira, Oliveira Silveira and Lelia Gonzalez). The proposal was understand through the historiographical review and oral history, the implications political and pedagogical (teaching of history) of the choices of activist intellectuals and black "militants" on the interpretations of the experiences of black resistance and the construction of meanings of the ascension of Zumbi dos Palmares as a black brazilian hero.